2002
DOI: 10.1046/j.1365-2567.2002.01384.x
|View full text |Cite
|
Sign up to set email alerts
|

Developmentally regulated interactions of human thymocytes with different laminin isoforms

Abstract: SUMMARYThe gene family of heterotrimeric laminin molecules consists of at least 15 naturally occurring isoforms which are formed by five different a, three b and three c subunits. The expression pattern of the individual laminin chains in the human thymus was comprehensively analysed in the present study. Whereas laminin isoforms containing the laminin a1 chain (e.g. LN-1) were not present in the human thymus, laminin isoforms containing the a2 chain (LN-2/4) or the a5 chain (LN-10/11) were expressed in the su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
35
2
3

Year Published

2005
2005
2022
2022

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(42 citation statements)
references
References 39 publications
2
35
2
3
Order By: Relevance
“…Using immunofluorescent staining with antibodies specific for individual LN-5 chains, we found LN-5 consisting of ␣3, ␤3 and ␥2 chains almost exclusively in the medulla of the human thymus, thus corroborating earlier results (Vivinus-Nebot et al, 1999;Kutlesa et al, 2002a). It was proposed that LN-5 is synthesized by medullary thymic stromal cells as part of their secreted ECM (Kutlesa et al, 2002a), but high-resolution light microscopy now revealed that LN-5 is found in highly organized bi-membranous structures (Fig.…”
Section: Molecular Characterization Of Human Thymic Conduitssupporting
confidence: 89%
See 3 more Smart Citations
“…Using immunofluorescent staining with antibodies specific for individual LN-5 chains, we found LN-5 consisting of ␣3, ␤3 and ␥2 chains almost exclusively in the medulla of the human thymus, thus corroborating earlier results (Vivinus-Nebot et al, 1999;Kutlesa et al, 2002a). It was proposed that LN-5 is synthesized by medullary thymic stromal cells as part of their secreted ECM (Kutlesa et al, 2002a), but high-resolution light microscopy now revealed that LN-5 is found in highly organized bi-membranous structures (Fig.…”
Section: Molecular Characterization Of Human Thymic Conduitssupporting
confidence: 89%
“…Rather, a network of interconnected TECs that permeates the cortex and the medulla of the thymic lobules has been suggested to provide a matrix for the migration of thymocytes (Ushiki, 1986;Prockop et al, 2002;Petri, 2003). Important constituents of the ECM of the thymus belong to the laminin family of basement membrane molecules (Kim et al, 2000;Magner et al, 2000;Geberhiwot et al, 2001;Kutlesa et al, 2002a). Laminins are heterotrimeric molecules consisting of ␣, ␤ and ␥ chains.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…LN is known to interact with Integrin α6β1 and integrin α6 is expressed in the absence of c-Myb ( Figure 28B). α9β1 has been reported to be a receptor for laminin in humans [335] and expression of Itga9 is predicted to be increased in the absence of c-Myb. Thus, it is possible that an increased expression of Itga9 alters interaction with laminin.…”
Section: Btg1mentioning
confidence: 99%